EMG gait data from indwelling electrodes is attenuated over time and changes independent of any experimental effect. (October 2020) - Reeves, Joanna; Starbuck, Chelsea; Nester, Christopher
Abstract: The effect of time on the validity of electromyography (EMG) signals from indwelling fine-wire electrodes has not been explored. This is important because experiments using intramuscular electrodes are often long and biochemical and mechanical factors, may impair measurement accuracy over time. Measures over extended periods might therefore be erroneous. Twelve healthy participants (age = 33 ± 8 years) walked for 50 min at a controlled speed. Fine-wire electrodes were inserted into tibialis anterior and a surface EMG sensor attached near the fine-wire insertion site. EMG signals progressively and significantly decreased with time with the fine-wire electrode, but not the surface electrode. For the fine-wire electrode, after 25 min mean amplitude had reduced by 11% (p < 0.001) and after 50 min by 16% (p < 0.001), and peak amplitude reduced 22% at 20 min (p = 0.006) and 37% at 50 min (p < 0.001). Reduced amplitude with indwelling EMG without concurrent changes in surface EMG signal suggests an important inconsistency in data from fine-wire EMG electrodes. Changes in EMG signal will occur over time independent of the experimental condition and this questions their use in experiments of more than 30 min. These results should impact on experimental study design. They also invite reinterpretation of prior literature and sensor innovation to improve measurement performance.